غرر کے محرّم معاملات: احادیث کی روشنی میں تحقیقی جائزہ: Prohibited Transactions Involving Gharar: A Research Study in the Light of Ahadith - Dr. Muhammad Aamir; Dr. Maaz Aziz (Al Manhal Research Journal, 2025)
Human beings naturally strive to secure their needs and advance their well-being, yet this pursuit often leads some individuals to resort to deception and unfair practices. Islamic law firmly prohibits such conduct and condemns all forms of fraud, uncertainty, and exploitation. Among these prohibited elements is Gharar—a type of excessive ambiguity or uncertainty that invalidates contractual agreements in Shariah. This paper examines the concept of Gharar in Islamic jurisprudence and analyzes various transactions forbidden in the Prophetic traditions due to their association with Gharar. Through a review of relevant Ahadith, the study highlights how Islamic teachings seek to promote transparency, fairness, and ethical conduct in financial dealings.